(untitled) (International Journal of Engineering and Computer Science, 2018)
The present paper evaluates motif shape patterns on Local Directional Pattern for texture classification. In this method Local Directional Pattern is computed on the image and then motif shape parameters are evaluated. These shape patterns are used as features for classification. The present method extensively tested on the Dataset consists of various brick, granite, and marble and mosaic stone textures collected from Vistex, Mayang database and also from natural resources from digital camera. The experimental results demonstrate that it is simple and much more effective than the other methods for texture classification.